Penambahan Tepung Sagu dan Tepung Terigu pada Pembuatan Roti Manis - Makmur, Satria A (Universitas Gorontalo, 2018)
Expect this research can provide information about the utilization of sago flour becomes economically benilai products that can be used in the manufacture of food products and then give you information on how to manufacture of sago flour with sweet bread. This research was carried out in the laboratory of Agricultural Technology Courses in February of the year 2017. The materials used in this study was powdered sugar, instant yeast, milk powder, salt, emulsifier, fresh milk, flour and sago appropriate treatment, egg yolks, butter and water ice. While the instrument used was a knife, a plastic sink, oven, baking pans, mixers, Cain and scales. This research method using a complete randomized design (RAL) consisting of three treatment addition of sago flour with wheat flour as much as 3 times. a sweet bread in the produce in a test of water content, rate of carbohydrates and organoleptic (taste, colour, texture and aroma) of research results of research regarding the addition of hasi flour with flour in bread making sago sweet get averages ? average water content (33.30%) levels of carbohydrates (61.45%) on different treatment ? different. A test of the level of fondness toward color, flavor, aroma and texture the highest results contained on the A3 where a 50% wheat flour and sago flour 50% because many of the panelists liked the organoleptic. Keywords : Sago Flour, All Purpose Flour, Bread Flour, The Addition Of Sago